Studi Eksploratif Kebutuhan Pembelajaran Daring untuk Mata Kuliah Menyimak pada Masa Pandemi Covid-19 - Elvrin Septyanti; Otang Kurniawan (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2020)
The purpose of this research is to describe the needs of students of the Indonesian Language and Satra Education study program related to the aspects of reading materials and platforms that can facilitate the online learning process during the Covid-19 pandemic. The method used in this study is a qualitative exploratory method with an inductive approach. Through this method, data is obtained based on questionnaire documentation distributed via google form. The research sample was obtained through purposive sampling technique from three universities in Riau: Riau University, Suska Riau Islamic State University, and Riau Islamic University. Furthermore, this study uses thematic data analysis techniques to identify themes through the results of the questionnaire to find important or interesting patterns from the data and use these to discuss or find the purpose of this study. The results of the analysis show that students need teaching materials in the form of audio in the form of narrative voices to hone and test their listening skills specifically for listening only. Then, students also need to listen to audio-visual in the form of videos to hone and test the overall listening power of these students. Because during the Covid-19 pandemic, all the things needed to listen to that which were of great interest to students were published online through digital classes with the Google Classroom platform. This is evidenced by the results of a survey of 64% of students requiring online learning with audio, visual, audio-visual teaching materials through Google Classroom digital classes. The results of this need are used to develop learning materials as a form of innovative learning products during the Covid-19 pandemic on campus.